Effects of vitamin C and folic acid supplementation on serum paraoxonase activity and metabolites induced by heat stress in vivo - Gursu, MF; Onderci, M; Gulcu, F; Şahin, Kazım (Pergamon-Elsevier Science Ltd, 2004)
This study investigated the effects of vitamin C (L-ascorbic acid) and folic acid supplementation on the levels of enzymes activities such as paraoxonase (PON1) and arylesterase and metabolites in the plasma of heat-stressed Japanese quails (Coturnix coturnix japonica) kept at 34degreesC. A total of 150 Japanese quails (10 days old) were randomly assigned to five treatment groups, with three replicates of 10 birds each. The birds, which were kept at 34degreesC (09.00 to 17.00; for 8 hours) were fed either a basal diet (high-temperature basal diet, HS group) or the basal diet supplemented with either 250 mg of L-ascorbic acid/kg of diet (Vit C group), 1 mg of folic acid/kg of diet (FA group), or 250 mg of L-ascorbic acid plus I mg of folic acid/kg of diet (Vit C + FA group), whereas birds kept at 22degreesC were fed a basal diet (thermo-neutral-basal diet, TN group). Supplemental vitamin C and folic acid significantly increased paraoxonase, arylesterase, creatine kinase, lactic dehydrogenase, and alkaline phosphatase activities compared with the HS group. Serum activities of aspartate aminotransferase and alanine aminotransferase were not influenced by dietary vitamin C or folic acid (P > 0.05). Serum cholesterol, triglyceride, high density lipoprotein (HDL)-cholesterol, and glucose concentrations decreased, whereas total protein and albumin concentrations increased with dietary vitamin C and folic acid supplementation (P < 0.05) compared with the HS group. However, the combination of vitamin C and folic acid provided the greatest results. Serum values were also greatest for PON1 and arylesterase and lowest for cholesterol, trygliceride, HDL-cholesterol and glucose (P < 0.05) for the TN group. The results of the study show that, separately or in combination, vitamin C and folic acid supplementation improved increased PON1 and arylesterase; the results also suggest that vitamin C and folic acid, especially in combination, may offer a potential protective management practice in preventing heat-stress-related depression in the performance of broiler quails. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: quails; heat stress; vitamin C; folic acid; PON1 arylesterase; HDL-cholesterol